Residential therapeutic communities for female substance abusers. - De Leon, G. (1991)
Therapeutic communities provide a unique model for the needs of chemically dependent mothers who are pregnant or of child bearing age. These programs have been treating female addicts, many of whom reflect the profile and needs of the current generation of addicted mothers in clinical problems, social disadvantages, and poor socialization. Specific issues of their recovery can be most efficiently addressed in a residential community that provides housing and a comprehensive approach including medical, social, psychological care, parental training, and child care. Most evident is that these women need a lifestyle change, an opportunity for maturation. In this regard, the therapeutic community offers the essential element of community as a setting for learning right living.